2022
DOI: 10.3390/ijerph19031663
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol, Perceived Stress, and the Effect of Group Dynamics: A Longitudinal Study of Young Men during Compulsory Military Training in Lithuania

Abstract: Previous research shows a nonlinear dependency between hair cortisol concentrations and perceived stress levels. This may be due to stress being targeted at the individual level despite it also being a social phenomenon which is often affected by group dynamics. Therefore, the objective of this study was to determine the influence of perceived stress on the hair cortisol level, considering the impact of the variables of group dynamics (interpersonal, task, and norm cohesion). Information was collected on 11 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The results of our study confirmed the insights of previous studies -that is, the military organizational dimension (C), which, according to a literature review, can be defined as a military unit-level, can affect soldiers' resilience and has the greatest impact on development of the active-duty soldiers' individual resilience by C1 -a positive command climate (Castro, 2007;Campbell D., Campbell K., & Ness, 2008;Paton, 2006;Smaliukiene et al, 2022) C2 -teamwork (Jue et al, 2020;Bekesiene et al, 2022), and C3 -cohesion (Lambić et al, 2018;Salo, 2008;Jue et al, 2020;Bekesiene et al, 2022;Smaliukiene et al, 2022). According to the development of psychological resilience, specific unit-level factors of military organization have a significant bearing on other aspects of resilience promotion resources.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our study confirmed the insights of previous studies -that is, the military organizational dimension (C), which, according to a literature review, can be defined as a military unit-level, can affect soldiers' resilience and has the greatest impact on development of the active-duty soldiers' individual resilience by C1 -a positive command climate (Castro, 2007;Campbell D., Campbell K., & Ness, 2008;Paton, 2006;Smaliukiene et al, 2022) C2 -teamwork (Jue et al, 2020;Bekesiene et al, 2022), and C3 -cohesion (Lambić et al, 2018;Salo, 2008;Jue et al, 2020;Bekesiene et al, 2022;Smaliukiene et al, 2022). According to the development of psychological resilience, specific unit-level factors of military organization have a significant bearing on other aspects of resilience promotion resources.…”
Section: Discussionsupporting
confidence: 89%
“…Jue et al, 2020;Bekesiene et al, 2022;Smaliukiene et al, 2021;Cohesion (C3) Capability of a unit to carry out joint tasks; sticking together, keeping a pledge to each other, and being committed to the mission. Lambić , 2018;Salo, 2008;Jue et al, 2020;Bekesiene et al, 2022;Smaliukiene et al, 2022;…”
Section: Speckhardmentioning
confidence: 99%
“…According to social cognitive theories ( Bandura, 1997 ) academic self-concept and self-efficacy can play a significant role in determining one’s motivation, perseverance, and resilience ( Djourova et al, 2020 ; Bekesiene et al, 2022 ; Kanapeckaitė et al, 2022 ; Bekesiene et al, 2023 ). As military professionals often encounter high-stress situations that require quick decision making and effective problem-solving ( Myrseth et al, 2018 ; Smaliukiene et al, 2022 ), the strong self-efficacy helps them manage stress by improving their belief in their ability to cope with and overcome challenges. This, in turn, can reduce anxiety, increase focus, and improve decision-making under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that research reveals a significant effect of socio-moral contexts in military organizations, ranging from highly motivating such as cohesion and esprit de corps ( Gal and Mangelsdorff, 1991 ) to undermining ones related to trauma, threats to personal safety violence ( van Voorhees et al, 2018 ). Studies show that camaraderie and mutual support make military service a subjectively meaningful activity ( Roth, 2021 ; Smaliukienė et al, 2022 ).…”
Section: Measuring Meaning In Military Service By Reservists: Hypothe...mentioning
confidence: 99%